Who Are the Unbanked? - Djankov, Simeon; Miranda, Pedro; Seira, Enrique; Sharma, Siddharth (World Bank, Washington, DC, 2012)
This paper uses nationally representative survey data from Mexico to compare households with savings accounts in formal financial institutions to their neighbors who do not have such accounts. The survey, which was conducted in 2005, contains information on nearly 5,000 households. The findings show that although neighboring banked and unbanked households have similar demographic and occupational profiles, the former are more educated and have markedly greater wealth. The median banked household spends 32 percent more per capita than the median unbanked household, and the median per capita wealth in banked households is 88 percent higher than that in unbanked households. The findings suggest that education levels, wealth, and unobserved household attributes that might be correlated with wealth and education play a major role in explaining who is banked.